Partners in Reform : The Special Program of Assistance for Africa (SPA) - Jeffrey, Katz; Alison, Rosenberg (World Bank, Washington, DC, 2012)
It is essential to obtain a far more thorough understanding of how economic reforms affect household welfare, particularly the poor, and how households react to economic reform. It is therefore important to monitor the evolution of poverty levels and social conditions over time. The Working Group on Poverty and Social Policy in the Special Program of Assistance for Africa (SPA) has begun this monitoring process, and is supporting information gathering and analysis at the country level. This work will be expanded. Donor support for adjustment programs will continue to be the principal objective of SPA-3. It would be misleading to assume that SPA donors can address all the development issues that confront Africa. Ultimately, the resolution of these fundamental concerns will depend on the resolve and talent of the people and governments of Sub-Saharan Africa.